2005
DOI: 10.1021/ja051196b
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization of cis-1-(2-Naphthyl)-2-phenylethene in Methylcyclohexane at 77 K:  No Hula-Twist

Abstract: The cis-trans photoisomerization of cis-1-(2-naphthyl)-2-phenylethene (c-NPEA and c-NPEB) was studied in methylcyclohexane glass at 77 K. The progress of the reaction was followed by fluorescence spectroscopy. Formation of the extended trans conformer (t-NPEB) is revealed by the growth of sharp vibronic bands on the broad structureless fluorescence spectrum of c-NPE. Principal component analysis with self-modeling of a matrix consisting of spectra generated by irradiation of c-NPE at different excitation wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 18 publications
(22 reference statements)
1
30
0
Order By: Relevance
“…2b) (only minor changes of relative heights of some of the fine vibrational structures). The obvious conclusion of formation of stable conformer(s) of the trans isomer (based on UV absorption spectra) is similar to that reported earlier (based on fluorescence studies) (14). However, formation of such a stable product(s) is consistent with any one of the three reaction pathways: OBF around the double bond, HT of the benzylic C–H unit or HT of the C–H unit near the naphthyl group if a conformer mixture similar to that of the trans isomer is obtained.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…2b) (only minor changes of relative heights of some of the fine vibrational structures). The obvious conclusion of formation of stable conformer(s) of the trans isomer (based on UV absorption spectra) is similar to that reported earlier (based on fluorescence studies) (14). However, formation of such a stable product(s) is consistent with any one of the three reaction pathways: OBF around the double bond, HT of the benzylic C–H unit or HT of the C–H unit near the naphthyl group if a conformer mixture similar to that of the trans isomer is obtained.…”
Section: Resultssupporting
confidence: 90%
“…Recently, in a report on low temperature photoisomerization of stilbene derivatives (15), the need to choose and design systems carefully for such mechanistic studies was emphasized. It was pointed out that the only chosen system in the said report (14) is incapable of yielding information suitable for establishing or eliminating any of the above‐mentioned reaction mechanisms. In this paper, we report results of our investigation on low temperature photochemical reactions of isomers of 1 and related systems ( 2 and 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…If cis olefin is used instead of the triazole ring, the cis olefin may be isomerized to trans olefin under the UV required for the fluorescence measurements 16. In the resulting trans form, fluorescence may be different from that of the cis form,16 thus the cis – trans isomerization may complicate analysis of the fluorescence data. With the 1,2,3-triazole group, there is no opportunity of such isomerization.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, depending on the correct structural assignment to the c ‐NTE conformer that exists in EPA glass, either the HT or the OBT mechanism will account for the results. But, for c ‐NTE to undergo HT photoisomerization it would have to do so about the naphthylenic CH, the process that we ruled out in the parent c ‐NPE . More explicitly, for the OBT photoisomerization mechanism to be correct, the B conformer of c ‐NPE must be dominant in MCH, but the A conformer of c ‐NTE must be dominant in EPA.…”
Section: Introductionmentioning
confidence: 95%
“…We showed that at 77 K in glassy MCH the photoisomerizations of cis ‐1‐(2‐naphthyl)‐2‐phenylethene ( c ‐NPE, Scheme , that exists mainly as the B conformer and cis ‐1‐(3‐methyl‐2‐naphthyl)‐2‐phenylethene ( c ‐3‐MPE) that should exist as the A conformer (Scheme , bottom left, proceed as shown by the OBT labeled pathways c ‐NPE B → t ‐NPE B and c ‐3‐MPE A → t ‐MPE A in Scheme . However, our conclusion that no HT is involved in those reactions was dismissed because HT photoisomerization about the benzylic CH would lead to the same result .…”
Section: Introductionmentioning
confidence: 99%